Nurturing the cultural desert: The role of museums in Singapore - HOE, Su Fern (Institutional Knowledge at Singapore Management University, 2018)
The absence of official platforms and institutions such as museums and visual arts spaces; while the artistic amateur scene was flourishing, there were no museums or national galleries where collections of the best local and regional artworks could be found, appreciated and studied by artists and citizens. This cultural desert was the result of the government’s attention to bread and butter issues. How, then, did Singapore transform from “cultural desert” of yesteryear to a city with 51 museums and 118 art galleries in 2013, as well as an arts scene that saw more than 3.2 million visitors to the national museums in the same year (Ministry of Culture, Community and Youth, 2014)? This chapter will focus on institutions for the visual arts such as museums, namely, the Asian Civilisations Museum the Singapore Art Museum, and the National Gallery Singapore. It will discuss these institutions as infrastructural projects and examine their broader ideological and political agenda such as positioning the city-state as a node between the greater Chinese and Indian civilisations, as well as to underline its status as a regional hub for the arts.